Find the greatest common divisor(GCD) of -1 and -1
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Theorem:
g cd ( 2 a − 1 , 2 b − 1 ) = 2 g cd ( a , b ) − 1 for some integers a , b .
Proof:
Let d = g cd ( 2 a − 1 , 2 b − 1 ) .
We have that g cd ( a , b ) is always a x + b y for some integers x , y .
We want to prove that d = 2 g cd ( a , b ) − 1 . It would be sufficient to prove that d ∣ 2 g cd ( a , b ) − 1 and 2 g cd ( a , b ) − 1 ∣ d .
1 ) We know that 2 a ≡ 1 ( m o d d ) and 2 b ≡ 1 ( m o d d ) , therefore 2 g cd ( a , b ) ≡ ( 2 a ) x ( 2 b ) y ≡ 1 ( m o d d ) . Hence d ∣ 2 g cd ( a , b ) − 1 .
2 ) We have 2 g cd ( a , b ) − 1 ∣ ( 2 g cd ( a , b ) ) k − 1 k = 2 a − 1 for some integer k . Similarly 2 g cd ( a , b ) − 1 ∣ 2 b − 1 . Hence 2 g cd ( a , b ) − 1 ∣ d .
( 1 ) ( 2 ) ⟺ d = 2 g cd ( a , b ) − 1 .